Quantum nature of non-Fermi charge carriers for pseudogap state of high-Tc superconductors - Sergeeva, G.G. (Вопросы атомной науки и техники, 2007)
For pseudogap state of underdoped cuprates high temperature superconductors (HTS) with stripe structure of copper-oxygen plane an approach for describing of U-stripe as two-dimensional state with vortex-like excitations is developed. At high temperatures these vortices are pinned by copper-oxygen complexes in U-stripes, and at lowering temperature the transition of pinned vortices to moving ones occurs at T ≤ Tf(p) where p is doping concentration. It is shown that this transition is the result of quantum diffusion which for quantum crystals was predicted by A.F. Andreev and I.M. Lifshits (1969). Quantum diffusion leads to non-Fermi charge carriers, and to two universal lines for common phase diagram of underdoped cuprates. This consideration let us to suppose that pseudogap state of underdoped cuprates is determined only by properties of copper-oxygen plane.